Quaternary terrestrial microvertebrates from mediterranean northwestern Africa: State-of-the-art focused on recent multidisciplinary studies. (15th November 2019) - Stoetzel, Emmanuelle; Lalis, Aude; Nicolas, Violaine; Aulagnier, Stéphane; Benazzou, Touria; Dauphin, Yannicke; El Hajraoui, Mohammed Abdeljalil; El Hassani, Ahmed; Fahd, Soumia; Fekhaoui, Mohammed; Geigl, Eva-Maria; Lapointe, François-Joseph; et al.
Abstract: Northwestern Africa is today characterized by high geographical, climatic and ecological diversity; it is recognized as a hotspot of biodiversity and a major area for both human and faunal evolution. Studies of North African fossil microvertebrates have increased considerably in recent years, but they no longer just provide palaeontological descriptions of the species found in the assemblages. They also aim at better understanding the evolution of faunal communities in relation to Quaternary climate changes and at reconstructing the palaeoenvironmental background of prehistoric human occupations, in well-established taphonomic and chronological contexts. These studies are also increasingly adopting an integrative approach by combining archaeology, palaeontology, (palaeo)genetics, taphonomy, palaeoecology and systematics, and using new methods such as geometric morphometrics and isotopic analyses on both fossil and modern specimens. This paper aims to present a history of the studies on Quaternary terrestrial microvertebrates from northwestern Africa, and show how recent multidisciplinary studies have provided new perspectives and evidence on the respective influences of climate change and increasing human pressure on their evolution. Highlights: This paper brings an updated state-of-the-art on Quaternary North African microvertebrate studies. We highlight the interest of combining data from different disciplines (integrative approach). We especially explore the role of environmental and anthropogenic changes on the microvertebrate biodiversity in Morocco.